Efforts to Prevent Work Accidents When Loading And Unloading At KMP. Portlink - Paulina M Latuheru; Doharman Lumban Tungkup; Yulia Puspita Sari; Fisca Dian Utami (IWJ : Inland Waterways Journal, 2023)
Safety is a program made to the workers as well as employers attempt to prevent accidents by means of recognizing things that could potentially cause accidents as well as anticipatory action in case of accidents. The goal is to create a safe workplace so it can hit the lowest possible risk of accident. Formulated the problem in this research is a work accident prevention efforts while unloading at the MV.Portlink. The research was carried out during the period of sea practices 9 months on the ship where the author undertakes the work practices of the sea. The theory used in this research is the theory- theory, human resources management with regard to safety. The method carried out intensively, researchers participating in the long field. This type of research is qualitative, descriptive. Method of data collection is done by observation, interviews and literature study. Methods of data analysis used the assortment (triangulation), and continuously until it is saturated. From the results of this research should be known throughout a worker follows the safety training work done by the company and penggunanaan self protective tools should be an obligation for workers at the port so that all workers can avoid a fatal accident due to work.